PENGEMBANGAN PERANGKAT PEMBELAJARAN SAINTIFIK BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN LITERASI MATEMATIKA SISWA SMP/MTS DI LOMBOK BARAT - Masjudin, Masjudin; Zulkifli, Zulkifli; Sufriany, Erry; Muzaki, Ahmad (Media Pendidikan Matematika, 2020)
The problem and challenge of learning mathematics in West Lombok in particular and Indonesia in general is the low ability of students' mathematical literacy. The findings of researchers in the field are that students' understanding of mathematics is a standard procedure for solving routine problems. Students have difficulty solving problems in the form of mathematical applications in everyday life. Therefore, efforts are needed to improve students' abilities in the process of constructing, simplifying, and compiling mathematical models, as well as their use in solving everyday problems. One thing that can be done is to simplify the mathematical concept into a series of activities in accordance with the sequence of students' knowledge development by using environmental media as a learning medium. Such a learning concept is scientific learning based on local wisdom. The purpose of this research is to produce scientific learning tools based on local wisdom that can improve the mathematics literacy skills of SMP / MTs students in West Lombok Regency. This type of research is Development Research. This research procedure carried out by referring to the 4-D Model, namely the Define stage, the Design stage, the Develop stage, and the Disseminate stage. The results of the validation show that local wisdom-based scientific learning tools are in the very valid category. The test results show that local wisdom-based scientific learning tools are very effective in improving the mathematics literacy skills of SMP / MTs students in West Lombok.